2013
DOI: 10.1177/0894439313497469
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Digital Skills in the Formation of Generalized Trust Among Latinos and African Americans in the United States

Abstract: A number of scholars have noted a digital skill divide among racial and ethnic groups in the United States (e.g. Hargittai, 2002). The ability to leverage information communication technologies (ICTs) in productive ways has been linked to greater levels of prodemocratic attitudes and behaviors (Horrigan, Wellman, & Rainie, 2006; Valenzuela, Park, & Kee, 2009; Vitak et al., 2011). However, no work to date has explored how this relationship between digital skills and political behavior is mediated by racial and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“…We compared this finding with several relevant papers regarding other factors that can affect a person's trust in using internet sites and providing personal information. A study proved that a person's trust in social media is influenced by digital skills possessed by a person [20] [21] [22]. Another study found that the greater the number of social media users, the greater their trust in people on social media [20] [23].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We compared this finding with several relevant papers regarding other factors that can affect a person's trust in using internet sites and providing personal information. A study proved that a person's trust in social media is influenced by digital skills possessed by a person [20] [21] [22]. Another study found that the greater the number of social media users, the greater their trust in people on social media [20] [23].…”
Section: Discussionmentioning
confidence: 99%
“…A study proved that a person's trust in social media is influenced by digital skills possessed by a person [20] [21] [22]. Another study found that the greater the number of social media users, the greater their trust in people on social media [20] [23]. Someone chooses to use social media to build or maintain social connections.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Monforti & Marichal (2014) studied digital skills and generalized trust in different ethnic groups: Latinos, African Americans and Anglo-Americans in the US. They found that digital skills were associated with generalized trust for African Americans but not for Latinos or Anglo-Americans.…”
Section: Resultsmentioning
confidence: 99%
“…Most of the studies they found indicated that social media has a positive effect on trust. Monforti and Marichal (2014) studied digital skills and generalised trust in different ethnic groups: Latinos, African-Americans and Anglo-Americans in the US. In this study, they found that digital skills were connected to generalised trust for African Americans but not for Latinos or AngloAmericans.…”
Section: Political Marketing Using Social Media Voter Trust and Votementioning
confidence: 99%